EFEKTIVITAS PELAYANAN PUBLIK PASCA PEMEKARAN (Suatu Studi Di Kecamatan Kawangkoan Utara Kabupaten Minahasa) - NAJOAN, ERWIN BELLY; RURU, JOORIE MARHAEN; MAMBO, RULLY (Sam Ratulangi University, 2018)
Abstract: Rise of the blossoming decade shows the magnitude of the last public attention will be the fulfillment of needs against the importance of the improvement of quality of service onthul. Already an open secret that these, low quality resources apparatus still. IT was based on the background of the issue, to find out the effectiveness of this research aims at servicing openbare Kawangkoan sub-district post extraction in the Regency of Minahasa Regency North Minahasa. This qualitative research methods. It is intended for the use of the method of obtaining answers to problems that are associated with the service that was provided to the implementation process of openbare Oleg Kawangkoan Subdistrict North of Apparatus to the community. The results showed the execution of existing services in openbare Cantor camat Kecamatan North Kawangkoan still need to be improved. The quality of the implementing Ministry apparatus openbare Kawangkoan in district North be concentrated the main elements of the BBC respondents for the study. Disimping it's the quality of the implementing apparatus resource stewards openbare Kawangkoan Kacamatan Cantor in the North being the main elements got the attention of BBC respondents for the study. In addition, resources should be noted. Ministry paratur Officers are less able to understand what the duties and responsibilities.Â Â Keywords: Effectiveness of Public Services, Service Quality, Regional Expansion